Michael Reactions of Alpha-Unsubstituted Trisubstituted 1H-Pyrroles - Lüönd, Rainer Martin; Neier, Reinhard (My University, 1991)
To obtain stable derivatives of alpha-unsubstituted pyrroles, the reaction of the test pyrrole 9 with a series of chalcones 14a-h were studied. Michael adducts 16b-h could be isolated. In order to synthesize coloured derivatives, the reaction of different pyrroles 9, 21, 23, and 25 with diphenylpropynone 19 was investigated. In these cases, too, Michael-addition products were formed. The intense absorption band around 400 nm makes the identification of these derivatives easy.